A survey on student acceptance of e-Learning at UiTM Pulau Pinang / Chow Shiao Huey, Ng Set Foong and Salwah Che Mat - Huey, Chow Shiao; Foong, Ng Set; Che Mat, Salwah (2007)
e-Leaming has become a necessity among Malaysian universities in order to be competitive. Universiti Teknologi MARA (UiTM) launches its e-leaming system known as i-Learn on 31st December 2005. However, i-Learn is yet to open for usage of student in UiTM Pulau Pinang (UiTM PP). Numerous researches abroad and local have indicated that effectiveness of e-learning depends mostly on student’s behaviour. This study therefore conducted an observational survey to investigate student readiness in accepting e-Learning in UiTM Pulau Pinang. Multistage cluster sampling was adopted with a total sample size of 180. A supervised self-administered questionnaire adopting group administration was then developed. There are eight sections totaling 42 questions in the questionnaire, namely demographic, ICT infrastructure availability and accessibility, information technology literacy, e¬learning experiences, e-learning acceptance, course pedagogy, e-learning functions and training necessities. Pretesting, pilot testing, face and content validity assessment were conducted prior to data collection with positive results. Reliability and statistical analysis was conducted on the survey data. Moderate to high inter split-half reliability was found for the questionnaire. Statistical analysis using SPSS reported that the student acceptance on e-learning at UiTM PP is low with only 38.7% preferring e¬learning. Demographic, ICT infrastructure availability and accessibility, e-learning experiences were found not to affect the student acceptance on e-learning except information technology literacy. Based on the findings of the survey, recommendations to i-Learn Centre (i-Lec) are made in hope to improve the student acceptance on i-Learn in UiTM PP.